Estudo de caso da parceria público-privada dos 'complexos hospitalares' do Estado de São Paulo: da manifestação de interesse privada - MIP aos principais desafios da modelagem - Tafur, Diego Jacome Valois (2017)
This work aims the case study about private-public partnership, ruled by Lei nº 11.079/2004, about public concession for construction, ‘gray coat’ and São Paulo hospital complex maintenance. Therefore all public procedure was analyzed for the development and execution, including the Private Expression of Interest, the São Paulo Government providences for the private-public partnership conclusion, the bidding procedure and final agreement for the contract. From the analysis it was possible to detect particularities for each stage of the public contract, especially about risks pointed by the private partner, like managing risks among ‘white coat’ services, medical team responsibilities, and ‘gray coat’ services, private partner responsibilities. This mentioned risk presence proves that political and social factors are elements of the project model, being up to the developers to make compatible the interests through the right contractual structure. At last, info and critical analysis about the highlights during the public procedure will be presented.